Uji Validitas International Standard Of Serial Number (Issn) Online Or E-Issn Menggunakan Aritmatika Modulo - Desi Rose Hertina; Max Teja Ajie Cipta Widiyanto (KILAT, 2019)
According to the history of coding (or encryption) data and information were carried out during the time of Julius Caesar, who used simple cryptographic techniques to protect his messages from the eyes of the enemy. In this paper a study will be conducted on the issuance of ISSN (International Standard of Serial Number) 10 sample journals The Scientific Information and Documentation Center (PDII) LIPI has the duty and authority to monitor all periodical publications published in Indonesia. As part of these responsibilities, PDII publishes an International Standard of Serial Number (ISSN), which is a unique identifier of each periodic publication that applies globally. The ISSN is granted by the ISDS (International Serial Data System) which is based in Paris, France. The ISSN was adopted as the implementation of ISO-3297 in 1975 by Subcommittee no. 9 of the Technical Committee no. 46 of ISO (TC 46 / SC 9). ISDS delegates the provision of ISSN both regionally and nationally. The Asian region is centered on the Thai National Library, Bangkok, Thailand. PDII LIPI is the only ISSN National Center for Indonesia. To do the validity test the E-ISSN code uses the Modulo algorithm.